Odpowiedzi

2010-02-25T17:14:24+01:00
3x + 2 = 2x + 5
3x - 2x = 5 - 2
x = 3

3x - 15 = x -3
3x - x = 15 - 3
2x = 12 |:2
x = 6

4(x + 1) = 6x
4x + 4 = 6x
4 = 6x - 4x
4 = 2x
2x = 4 |:2
x = 2

3(x+1) = 2(2x + 1)
3x + 3 = 4x + 2
3 - 2 = 4x - 3x
1 = x

3(2x-1)-2(4x+3)=7-4(x+1)
6x + 3 - (8x + 6) = 7 - (4x + 4)
6x + 3 - 8x - 6 = 7 - 4x - 4
6x - 8x + 4x = 7 - 4 - 3 + 6
2x = 6 |:2
x = 3
2010-02-25T17:14:32+01:00
3x+2=2x+5
3x-2x=5-2
x=3

3x-15=x-3
3x-x=-3+15
2x=12:2
x=6

4(x+1)=6x
4x+4=6x
4x-6x=4
-2x=4:(-2)
x=-0,5

3(x+1)=2(2x-1)
3x+3=4x-2
3x-4x=-2-3
-x=-5:(-1)
x=5

3(2x-1)-2(4x+3)=7-4(x+1)
6x-3-8x+6=7-4x+4
6x-8x+4x=7+4+3-6
2x=8:2
x=4
2010-02-25T17:15:53+01:00
3x+2=2x+5 |-2
3x=2x+3 |-2x
x=3

3x-15=x -3 |+15
3x=x+12 |-x
2x=12 |:2
x=6

4(x+1)=6x
4x+4=6x |-4
4x=6x-4 |-6x
-2x=-4 |:(-2)
x=2

3(x+1)=2(2x-1)
3x+3=4x-2 |-3
3x=4x-5 |-4x
-x=-5 |:(-1)
x=5

3(2x-1)-2(4x+3)=7-4(x+1)
6x-3-8x-6=7-4x-4
-2x-9=3-4x |+9
-2x=12-4x |+4x
2x=12 |:2
x=6